The relation between the atrial blood supply and the complexity of acute atrial fibrillation. (June 2021) - Dudink, Elton A.M.P.; Bidar, Elham; Jacobs, Judith; van Hunnik, Arne; Zeemering, Stef; Weijs, Bob; Luermans, Justin G.L.M.; Maesen, Bart A.E.; Cheriex, Emile C.; Maessen, Jos G.; Hoorntje, Jan C.A.; Schotten, Ulrich; et al.
Abstract: Background: Patients with a history of myocardial infarction and coronary artery disease (CAD) have a higher risk of developing AF. Conversely, patients with atrial fibrillation (AF) have a higher risk of developing myocardial infarction, suggesting a link in underlying pathophysiology. The aim of this study was to assess whether coronary angiographic parameters are associated with a substrate for AF in patients without a history of AF. Methods: During cardiac surgery in 62 patients (coronary artery bypass grafting (CABG;n = 47), aortic valve replacement (AVR;n = 9) or CABG + AVR (n = 6)) without a history of clinical AF (age 65.4 ± 8.5 years, 26.2% female), AF was induced by burst pacing. The preoperative coronary angiogram (CAG) was assessed for the severity of CAD, and the adequacy of atrial coronary blood supply as quantified by a novel scoring system including the location and severity of right coronary artery disease in relation to the right atrial branches. Epicardial mapping of the right atrium (256 unipolar electrodes) was used to assess the complexity of induced AF. Results: There was no association between the adequacy of right atrial coronary blood supply on preoperative CAG and AF complexity parameters. Multivariable analysis revealed that only increasing age (B0.232 (0.030;0.433), p = 0.03) and the presence of 3VD (B3.602 (0.187;7.018), p = 0.04) were independently associated with an increased maximal activation time difference. Conclusions: The adequacy of epicardial right atrial blood supply is not associated with increased complexity of induced atrial fibrillation in patients without a history of clinical AF, while age and the extent of ventricular coronary artery disease are.